PENGARUH ICE BREAKING TERHADAP MOTIVASI SISWA PADA PEMBELAJARAN PJOK DI SMP SWASTA ADVENT BARUS JULU - Fitri Wati Op.Sunggu; Tri Widia Astuti Tamba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of implementing ice breaking activities on students' motivation in Physical Education, Sports, and Health (PJOK) learning at Advent Barus Julu Private Junior High School. This research used a quantitative approach with pre-experimental method and one-group pretest-posttest design. The population was all seventh-grade students, with a sample of 26 students selected through purposive sampling technique. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. Data analysis included descriptive statistics, normality test using Kolmogorov-Smirnov, and hypothesis testing using Paired Sample t-Test. The results showed that the average motivation score before treatment was 52.65 and increased to 57.88 after treatment, with a significance value of 0.004 < 0.05. It can be concluded that the implementation of ice breaking has a significant effect on students' motivation in PJOK learning.